Oral Candida colonization and anti-fungal susceptibility pattern in patients with hematological malignancy - Maryam Talebshoushtari Zadeh; Ensieh Lotfali; sara Abolghasemi; Mahsa Fattahi (Mazandaran University of Medical Sciences, 2022)
Background and Purpose: Candidiasis is considered as one of the most important fungal infections in hematological malignancy. Candidiasis is considered as the most important cause of disease and mortality in hematological malignancy and antifungal prophylaxis is important (remove highlighted text).Objectives: The aim of study is to identify and evaluated antifungal susceptibility pattern in patients with hematological malignancyMaterial and Methods: In this study, samples were collected from the oral cavity of 100 patients and Candida colonization was confirmed by fungal culture. Isolated Candida strains were identified by ITS-PCR. In vitro antifungal susceptibility tests against fluconazole (replace "fluconazole" with "azoles"), amphotericinB and caspofungin were performed according to CLSI M27-A3/S4. Results: Demographics, comorbidities, distribution of Candida species, antifungal susceptibility were analyzed. Study participants included 100 patients. The mean age of patients was 15.48% ±48.74 years were in the range of 17 to 84 years and in terms of sex distribution, 64% were male and 36% were female. In terms of the distribution of underlying hematologic malignancy, 27% had lymphoma. The most commonly isolated species among patients were 49% C. albicans, 31% C. glabrata, 10% Co-colonization of C. albicans and C. with C. glabrata .The overall resistance of C.albicance was %5 to fluconazole%2 to amphotericinB.C. glabrata showed %11 resistance to fluconazole and was susceptible to amphotericinB.All candida spp.isolated from patients were susceptible to caspofungin.Conclusions: The high rate of colonization of Candida species, especially the significant increase in the frequency of Candida glabrata in patients with blood malignancies and the gradual increase in resistance to fluconazole, necessitate a change in the use of antifungal drugs for the prevention and experimental treatment of hematological malignancy.